Muscle Contributions to L4-5 Joint Rotational Stiffness following Sudden Trunk Flexion and Extension Perturbations. (14th January 2013) - Cort, Joel A.; Dickey, James P.; Potvin, Jim R.
Abstract : The purpose of this study was to investigate the contribution of individual muscles (MJRSm ) to total joint rotational stiffness (MJRST ) about the lumbar spine'sL 4 - 5 joint prior to, and following, sudden dynamic flexion or extension perturbations to the trunk. We collected kinematic and surface electromyography (sEMG) data while subjects maintained a kneeling posture on a parallel robotic platform, with their pelvis constrained by a harness. The parallel robotic platform caused sudden inertial trunk flexion or extension perturbations, with and without the subjects being aware of the timing and direction. Prevoluntary muscle forces incorporating both short and medium latency neuromuscular responses contributed significantly to joint rotational stiffness, following both sudden trunk flexion and extension motions. MJRST did not change with perturbation direction awareness. The lumbar erector spinae were always the greatest contributor to MJRST . This indicates that the neuromuscular feedback system significantly contributed to MJRST, and this behaviour likely enhances joint stability following sudden trunk flexion and extension perturbations.